COMPARISON STUDY BETWEEN DUBININ-RED USHKEVICH AND TEMKIN MODEL FOR ADSORPTION OF MERCURY ONTO ACTIVATED CARBON (Journal of Engineering, 2008)
Activated carbon has been used as an adsorbent in this work to remove mercury from aqueous solutions. The aim of the work is to test how best activated carbon can be used as an adsorbent for mercury. Equilibrium isotherms, both, Dubinin-Redushkevich, and Temkin have been test. The batch experiments were conducted at room temperature (30oC) and at the normal pH (7.0±0.1) of the solution. HYBRID fraction error function analysis shows that the best-fit for the adsorption equilibrium data is represented by (D-R) model rather than Temkin model. Its found that the correction factor (R2) for (D-R) is 0.9928 while for Temkin model is 0.942, also the HYBRID fractional error was conducted for the both models and (D-R) model give minimum value of (0.0128) while it was (0.129) for Temkin.